The handbook of project management a practical guide to effective policies, Procedures - Young, Trevor L. (Trevor Leonard), 1940- (New Delhi : Kogan Page, 1999)
Fully revised and updated, this new edition includes an introduction to the concept of programme management, an outline of the relationship between programmes and projects, and a revision of the dynamic life cycle to include new ideas and opportunities.
Title from e-book title screen (viewed October 15, 2007).
Includes bibliographical references (p. 289-290) and index.
Also available in print.
Keywords: Project management